BAPTISM: A COMPARATIVE STUDY OF THE REFORMED AND PENTECOSTAL MODEL - Ekpenyong, Ekpenyong Obo; Ntamu, G. U. (European Scientific Journal, ESJ, 2014)
Baptism has been a mean of identifying with Christianity from the start and since the 16th century it has been one of those recurrent theological issues which have engaged Christians in debates. Genuine children of God truthfully come up to the same scriptures but often arrive at radically diverse conclusions. Jesus during his last task commanded the apostles as well as the church to “go…and make disciples of all nations, baptizing them in the name of the Father and of the Son and of the Holy Spirit”. The rite of baptism is practice, by all Christian Churches, and as well confesses that Baptism was instituted by the Lord Jesus as an abiding sign of admittance to His church. This work intends to explore here, the points of convergence and divergence between the Reformed model and the Pentecostal model of baptism. The paper shown among others that their major point of exit is that Pentecostal churches do not baptize infants. Rather, children in Pentecostal churches are dedicated to God and blessed and their mode of baptism is by immersion whereas Reformed baptize infants to initiate them into covenant with God and to integrate them into the visible church and their mode of baptism is by pouring or sprinkling.